A combined experimental and theoretical study of RuO2/TiO2 heterostructures as a photoelectrocatalyst for hydrogen evolution. Issue 11 (27th February 2023) - Kaikhosravi, Mohammad; Hadadzadeh, Hassan; Farrokhpour, Hossein; Salimi, Abdollah; Mohtasham, Hamed; Foelske, Annette; Sauer, Markus
Abstract : An experimental and theoretical study of RuO2 /TiO2  heterostructures as photoelectrocatalysts for hydrogen evolution reaction (HER). Abstract : We report a joint experimental and theoretical study of RuO2 /TiO2 heterostructures. In the experimental section, mesoporous RuO2 /TiO2 heterostructures were prepared by impregnation of mesoporous TiO2 nanoparticles which were synthesized from a new precursor, Na2 [Ti(C2 O4 )3 ], in an aqueous solution of ruthenium(III) chloride followed by calcination at 300 °C. Using various techniques, the prepared TiO2 and RuO2 /TiO2 heterostructures were extensively characterized. The photoelectocatalytic application of the as-prepared heterostructures was then investigated toward the hydrogen evolution reaction (HER). The results illustrated that RuO2 is dispersed uniformly on the TiO2 surface. The loading of RuO2 on TiO2 decreases the band gap energy and extends the absorption edge to the visible light region. This wide absorption extends the photoelectrocatalytic activity of RuO2 /TiO2 heterostructures. To obtain a deeper understanding of the increase of the photoelectrocatalytic activity of RuO2 /TiO2 heterostructures compared to pure TiO2, theoretical calculations at the density functional theory (DFT) level were performed on some model clusters of pure TiO2 and the RuO2 /TiO2 heterostructure. The theoretical results elucidated that the recombination ratio of electron–hole pairs decreases effectively for RuO2 /TiO2 compared to pure TiO2 .